2015
DOI: 10.1200/jco.2014.57.8401
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Ultrasound After Neoadjuvant Chemotherapy and Its Impact on Sentinel Lymph Node Surgery: Results From the American College of Surgeons Oncology Group Z1071 Trial (Alliance)

Abstract: Purpose The American College of Surgeons Oncology Group Z1071 trial reported a 12.6% false-negative rate (FNR) for sentinel lymph node (SLN) surgery after neoadjuvant chemotherapy (NAC) in cN1 disease. Patients were not selected for surgery based on response, but a secondary end point was to determine whether axillary ultrasound (AUS) after NAC after fine-needle aspiration cytology can identify abnormal nodes and guide patient selection for SLN surgery. Patients and Methods Patients with T0-4, N1-2, M0 breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
142
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(150 citation statements)
references
References 22 publications
7
142
0
1
Order By: Relevance
“…Negative axillary ultrasound (by central review) was associated with lower burden of disease in the axilla when the SLN remained involved. 8 Patients with a suspicious axillary ultrasound after NAC were significantly more likely to be SLN-positive at surgery (71.8%) than those with a normal axillary ultrasound (56.5%). Furthermore, patients with suspicious nodes by axillary ultrasound had a greater number of positive nodes and larger metastases (p \ 0.001).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Negative axillary ultrasound (by central review) was associated with lower burden of disease in the axilla when the SLN remained involved. 8 Patients with a suspicious axillary ultrasound after NAC were significantly more likely to be SLN-positive at surgery (71.8%) than those with a normal axillary ultrasound (56.5%). Furthermore, patients with suspicious nodes by axillary ultrasound had a greater number of positive nodes and larger metastases (p \ 0.001).…”
mentioning
confidence: 90%
“…Furthermore, patients with suspicious nodes by axillary ultrasound had a greater number of positive nodes and larger metastases (p \ 0.001). 8 Among the patients with positive SLNs at surgery after a normal axillary ultrasound, 63% had no additional positive nodes in the ALND specimen. These findings indicate that the use axillary ultrasound can be helpful in identifying patients who despite a positive SLN after NAC have lower residual tumor burden in non-SLNs.…”
mentioning
confidence: 95%
“…Recent studies have analyzed the performance of SLNB in patients that converted from a clinically suspicious sentinel lymph node (SLN) status before to a clinically negative SLN status after PST [1,2,3]. Overall, these studies demonstrated higher false-negative rates (SLN negative, axillary nodes positive) compared to the primary operative setting.…”
Section: Introductionmentioning
confidence: 99%
“…Three prospective studies have investigated the accuracy of SLNB after NAC in initially nodepositive patients and demonstrated variable FNRs; many were unacceptably high ([10 %) when the entire study population was included. [7][8][9] However, when patients with C3 SLNs were analyzed, the FNRs decreased to \10 % in most cases. With the suggested benefit of analyzing C3 SLNs, the differences in methodologies as well as a median number of 2 SLNs examined in these prospective trials, critics have questioned the feasibility of performing an accurate SLNB after NAC.…”
mentioning
confidence: 99%
“…9 All SLNs underwent central review by a single pathologist and were considered positive if any residual disease, including ITCs or micrometastases, was identified. Immunohistochemistry (IHC) was routinely used if initial H&E staining was negative.…”
mentioning
confidence: 99%